Epithelial HLA-DR expression and T lymphocyte subsets in salivary glands in Sjögren's syndrome. - Lindahl, G (1985)
Salivary glands obtained at biopsy from patients with Sjögren's syndrome and controls were studied with regard to phenotype of infiltrating and residing cells, by means of a double immunoenzymatic staining technique. The infiltrating lymphocytes, which were sparse or absent in the control group in contrast to their abundant presence in the Sjögren patients, consisted in both groups mainly of T lymphocytes, the majority of which were T helper cells. In the controls, the glandular epithelial cells were HLA-DR- whereas in the Sjögren patients HLA-DR+ epithelial cells were found, mainly confined to areas, where the epithelial cells were seen in close proximity to the periphery of dense lymphocytic infiltrates. The data are in accordance with recent findings of HLA-DR expressing residing cells in the target organs of various chronic inflammatory diseases and might indicate the induction of HLA-DR expression in nonlymphocytic cells of target organs in which a cellular infiltration dominated by cells of the T helper phenotype is found.